2022
DOI: 10.1111/nph.18643
|View full text |Cite
|
Sign up to set email alerts
|

Molecular module of CmMYB15‐like‐Cm4CL2 regulating lignin biosynthesis of chrysanthemum (Chrysanthemum morifolium) in response to aphid (Macrosiphoniella sanborni) feeding

Abstract: Lignin is a major component of plant cell walls and a conserved basic defense mechanism in higher plants deposited in response to aphid infection. However, the molecular mechanisms of lignin biosynthesis in response to aphid infection and the effect of lignin on aphid feeding behavior remain unclear.We report that 4-Coumarate:coenzyme A ligase 2 (Cm4CL2), a gene encoding a key enzyme in the lignin biosynthesis pathway, is induced by aphid feeding, resulting in lignin deposition and reduced aphid attack. Upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Afterward, the vectors of CaLCuV, PCVB, and CaLCuV‐ CmAFL1 were transformed into A. tumefaciens strain GV3101, respectively. The preparation of the infection suspension and the procedures for instantaneous conversion of chrysanthemums were performed as described before (Huang et al., 2022; Li et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, the vectors of CaLCuV, PCVB, and CaLCuV‐ CmAFL1 were transformed into A. tumefaciens strain GV3101, respectively. The preparation of the infection suspension and the procedures for instantaneous conversion of chrysanthemums were performed as described before (Huang et al., 2022; Li et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, the vectors of CaLCuV, PCVB, and CaLCuV-CmAFL1 were transformed into A. tumefaciens strain GV3101, respectively. The preparation of the infection Ó 2023 Society for Experimental Biology and John Wiley & Sons Ltd., The Plant Journal, (2023), 116, 1652-1666 CmTEM1-CmAFL1 module inhibits flowering 1663 suspension and the procedures for instantaneous conversion of chrysanthemums were performed as described before (Huang et al, 2022;Li et al, 2023).…”
Section: Virus-induced Gene Silencing Experiments In Chrysanthemummentioning
confidence: 99%
“…Different classes of avonoids and lignin are synthesized via the phenylpropanoid pathway [49]. Lignin is a structural component of the cell wall and the expression of its biosynthetic pathway genes enhance plant defense [50][51][52]. The expression of genes encoding key enzymes of the phenylpropanoid pathway was signi cantly upregulated following A. alternata infection in chrysanthemum (Fig.…”
Section: Ja Enhanced the Cell Wall Integrity Maintenance Systemmentioning
confidence: 99%
“…In addition to providing structural support, lignin is involved in plant defense against biotic and abiotic stresses (Kumar, Campbell, et al, 2016;Moura et al, 2010;Wang, Guo, et al, 2022). Studies have shown that the enhanced lignin biosynthesis in plants contributes to their resistance against citrus canker and aphid infestation (An et al, 2019;Li, Zhang, et al, 2023;Zhou, Yue, et al, 2021). Improved lignin content also enhances the drought and salt tolerance of plants (Chen, Guo, et al, 2020;Li, Yang, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%